Efektifitas Biolarvasida Dari Ekstrak Kulit Durian Montong Dengan Buah Jeruk Purut Terhadap Kematian Jentik Nyamuk - Muhammad Abdul Halim; Giesty Trienita; Widayoko, Agus (SMA Trensains Muhammadiyah Sragen, 2025)
Mosquitoes are one of the most disease-causing animals in Indonesia. Among the famous ones are Aedes aegypti, Aedes albopictus, and Aedes scutellaris, the vectors of the spread of dengue fever throughout 2024. There are many ways to cut mosquito breeding, one of which is using abate which contains harmful chemicals that impact environmental damage and trigger cancer. Therefore, a safe larvicide for humans and the environment is needed. The purpose of this research is to make a larvicide from durian and kaffir lime peel extracts that can cut mosquito breeding and reduce losses from mosquitoes. The research method used is the quantitative descriptive research method. Effectiveness indicators include organoleptic tests, pH tests, weight reduction tests, and mortality tests. The results of the organoleptic test showed that the water treated with larvicide was odorless, colorless, and non-irritating. The pH test showed a value of 8, the weight reduction test on mosquito larvae showed a weight reduction of 0,9% after being given the larvicide, and in the mortality test, 100% of mosquito larvae experienced death against the larvicide that had been given. So it can be concluded that this larvicide is safe for the environment and physical contact with humans.